2022
DOI: 10.1111/acer.14927
|View full text |Cite
|
Sign up to set email alerts
|

Cultural identity affiliation and alcohol use and related consequences among American Indian and White adolescents: A latent profile analysis

Abstract: Background: Adolescent alcohol use is a significant public health concern and rates of alcohol use are higher among American Indian (AI) adolescents than national samples of non-AI youth. A potential factor in understanding AI alcohol use is cultural identity, which can vary widely based on experiences of historical trauma. We used latent class analysis to examine cultural identity in AI and White adolescents and their alcohol use outcomes in relation to the latent class solutions. Methods:The samples included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
(80 reference statements)
2
1
0
Order By: Relevance
“…Our finding of a curvilinear association may help to explain previously observed mixed findings, as it may be that previous studies have largely modeled this association linearly, or only examined the effects of cultural affiliation among groups characterized by high or low drinking (thus, only seeing one side of the U). This finding is also consistent with Schick et al (2022), who similarly found evidence of a curvilinear association between cultural affiliation and alcohol‐related consequences, wherein adolescents reporting low and high cultural affiliation reported higher alcohol‐related consequences relative to a group reporting moderate cultural affiliation. Future research is needed to examine the nature of this association more precisely.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding of a curvilinear association may help to explain previously observed mixed findings, as it may be that previous studies have largely modeled this association linearly, or only examined the effects of cultural affiliation among groups characterized by high or low drinking (thus, only seeing one side of the U). This finding is also consistent with Schick et al (2022), who similarly found evidence of a curvilinear association between cultural affiliation and alcohol‐related consequences, wherein adolescents reporting low and high cultural affiliation reported higher alcohol‐related consequences relative to a group reporting moderate cultural affiliation. Future research is needed to examine the nature of this association more precisely.…”
Section: Discussionsupporting
confidence: 91%
“…However, in Study 1, this association was no longer significant once age and sex were added into the model, while the interaction remained significant even after controlling for covariates in Study 2. This finding adds to a mixed body of literature, wherein some studies find a protective effect of culture with respect to alcohol use (Goldstein et al, 2021;Tingey et al, 2016), while others do not find such an effect (Schick et al, 2022;Whitesell et al, 2014;Yu & Stiffman, 2007). Our finding of a curvilinear association may help to explain previously observed F I G U R E 1 Simple slope results for racial discrimination by cultural affiliation interaction predicting alcohol use (Study 1).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Therefore, it is an effective strategy to properly use annotation in the course of textbook compilation and teaching Illustration: Illustration is another important way of presenting culture in foreign language teaching materials. By displaying pictures, maps and charts related to Chinese culture, learners can have a more intuitive understanding of Chinese culture [4] For example, when introducing the geography of China, a map of China can be inserted in the textbook so that learners can have a clearer understanding of the geographical location, administrative divisions and geographical features of China. In addition, by displaying some representative Chinese cultural symbols, such as totems, calligraphy, and traditional Chinese painting, learners can better understand and appreciate the charm of traditional Chinese art.…”
Section: Cultural Presentation Modementioning
confidence: 99%